1996
DOI: 10.1016/s0022-5347(01)65490-9
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy for High Grade Clinically Localized Adenocarcinoma of the Prostate

Abstract: At 4 years the freedom from PSA failure following radiotherapy for high grade prostate cancer was comparable to previously reported surgical series. The high failure rate among patients with PSA greater than 20 ng./ml. suggests that these patients should be considered for investigational approaches. The apparent improvement in freedom from progression with the use of higher doses provides reason for optimism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(20 citation statements)
references
References 15 publications
2
18
0
Order By: Relevance
“…Patients reported here with higher Gleason score but low PSA still appeared to have a high likelihood of remaining biochemically free of disease, at least for those with Gleason scores below 8. This finding is in agreement with preliminary data from UCSF, where patients with Gleason scores of 8-10 had a low rate of early biochemical failure after EBRT if their PSA was below 20 ng/ml [11].…”
Section: Discussionsupporting
confidence: 91%
“…Patients reported here with higher Gleason score but low PSA still appeared to have a high likelihood of remaining biochemically free of disease, at least for those with Gleason scores below 8. This finding is in agreement with preliminary data from UCSF, where patients with Gleason scores of 8-10 had a low rate of early biochemical failure after EBRT if their PSA was below 20 ng/ml [11].…”
Section: Discussionsupporting
confidence: 91%
“…Results from other institutions using 3DCRT demonstrate similar bNED results when patients are stratified by pretreatment PSA [12,34,35]. At the University of Michigan, the 5-year actuarial rates of bNED were 88%, 72%, 43%, and 30%, respectively, for patients with pretreatment PSA values <4, 4-10, 10-20, and >20 ng/ml.…”
Section: Dose Escalation With 3dcrtmentioning
confidence: 63%
“…However, only pretreatment PSA, T stage, and Gleason score remained independent predictors on multivariate analysis [12]. Roach et al [34] reported the UCSF experience of treating 50 patients with high-grade (Gleason score 8-10) prostate cancer using 3DCRT. Patients treated with >71 Gy had 4-year rates of bNED control of 83% vs. 0% for those patients treated with conventional doses of radiation (<71 Gy) [34].…”
Section: Dose Escalation With 3dcrtmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight-year bRFS rate were 86% versus 86% (p = 0.16) for favorable-risk (T1 to T2a, GS < or = 6, PSA < or = 10 ng/ml) patients and 62% versus 61% (p = 0.96) for unfavorable-risk (T2b to T2c, GS > or = 7, PSA > 10 ng/ml) patients with RP versus those treated with RT > or = 72 Gy (Fig 1). Several study also have demonstrated that doses in excess of 70 to 72 Gy are associated with a reduction in the risk of recurrence compared with lower doses [8][9][10][11][12].…”
Section: Clinical Results Of 3d-crtmentioning
confidence: 99%